Ana Rios IPCC WGIII release event April 16 2014 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Agriculture and future climate in LAC: Systemic impacts and potential responses -- Ana Rios, Inter-American Development Bank Meeting global food needs with lower emissions: IPCC report findings on climate change mitigation in agriculture A dialog among scientists, practitioners and financiers April 16, 2014 World Bank, Washington, DC